Exercícios verdes e autoconversas: validação de escala e efeitos sobre o estresse e práticas sustentáveis - Souza, Thiago Siqueira Paiva de (2021)
This thesis aimed to analyze the relationships and effects of Green Exercises and self-talk about neurophysiological stress and sustainable socio-environmental practices. We hypothesized that individuals who practice green exercises and using self-talks will improve their sustainable practices, present lower internal loads, in addition to showing improvements in psychological states. The Thesis is composed of multiple methodological characteristics: translation, cultural adaptation, and validation; Systematic review, correlational descriptive study, and experimental. To analyze the experimental data, two-way ANOVA of repeated measures were used with analyzes of inter and intragroup; condition x time interaction effects, and Tukey's post hoc test with a significance level of p≤0.05, as well as observing the effect size (η) and observed power (1-β). For the validation of the self-talk questionnaire for sports, quality measures of useful adjustments were used for confirmatory factor analysis as well as Cronbach's Alpha reliability index. For the correlations, Pearson's bivariate, biserial point, and partial correlation were used, in the latter case, the correlations were controlled by age and sex. As a result, it can be said that after the process of translation and cultural adaptation, the S-TQ scale for sports (pt-br) obtained a good level of understanding, technical-scientific and similarity with the original scale, being able to the validation process. About the validation, the viability of the S-TQ pt-br was proved given the internal consistency of Cronbach's α = 0.947 and that all goodness-of-fit indices are within the standards recommended by the literature. Regarding green exercises and their physiological effects, after a systematic review it can be concluded that the practice of green exercises can potentiate the physiological effects in apparently healthy adults, collaborating with the health status and the sustainable well-being of their practitioners. After correlation analysis, it can be concluded that providing the population with a rapprochement with the natural environment for their practice of physical exercises can be beneficial both for the human species and the other animal and plant species present in Brazilian ecosystems, once that the highest number of hours per week in physical exercise in nature correlated with sustainable consumption and the use of self-talks even after this association was controlled by age and sex. The same result was not possible to observe in urban outdoor or indoor environments. Concerning experimental studies, it can be concluded that in 5km runs at a moderate pace, thermal discomfort, temperature, and air relative humidity does not affect the performance of practitioners, however, thermal comfort acts as a protective effect of physiological stress, while thermal discomfort raises the internal training load, promoting an increase in upper respiratory tract infections. This Thesis demonstrates the ecosystem benefits provided by natural environments for physical exercise practitioners even in tropical climate zones, as it concludes that green exercises minimize the effects of neurophysiological stress after physical activity with or without a cognitive activity of self-talk. These results can collaborate with health and sports professionals to plan more sustainable training, as well as can be used by urban planners, managers, and environmentalists for projects to expand and improve access to green areas in urban zones.